2013
DOI: 10.3892/etm.2013.1002
|View full text |Cite
|
Sign up to set email alerts
|

A case of ossifying fibroma of the frontal sinus

Abstract: Ossifying fibroma is a rare benign tumor of the nasal cavity and the paranasal sinus, and is easily misdiagnosed. In the present study, we report the clinical data in the case of a 46-year-old female patient, treated due to 5-day forehead swelling accompanied by dizziness. CT examination revealed dilation of the right frontal sinus, bone wall integration, dense masses in the cavity, multiple punctate calcification foci internally and no nasal obstruction, nasal mucus or epistaxis. After hospitalization, a righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…It may invade the eye socket, skull base and calvarium and may present with related symptoms, and its malignancy rate is (0.4-0.5%). As per the studies, it seems to induce by repetitive surgery or chemotherapy [11]. Regarding the age, rapid progression of the lesion and the radiographic features, the case bears similarity with JOF.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It may invade the eye socket, skull base and calvarium and may present with related symptoms, and its malignancy rate is (0.4-0.5%). As per the studies, it seems to induce by repetitive surgery or chemotherapy [11]. Regarding the age, rapid progression of the lesion and the radiographic features, the case bears similarity with JOF.…”
Section: Discussionsupporting
confidence: 56%
“…Patient needs to undergo redo surgery on recurrence. Radiotherapy and chemotherapy are not advised as it may transform the lesion into malignancy like osteosarcoma [11].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al reported on a 46-year-old female patient with ossifying fibroma [17]. CT scan showed dilation of the right frontal sinus and dense masses in the cavity.…”
Section: Discussionmentioning
confidence: 97%